LITERATURE REVIEW : SMART HOME BASED ON IOT FOR SECURITY SYSTEM - Baltra Agusti Pramajuri; Syaddam Syaddam; Try Hadyanto; Margret Ade Cipta Rahmani (Jurnal Teknologi dan Sistem Tertanam, 2023)
Security is an important aspect that must be considered from a house, building, and environment. The purpose is to avoid various types of crime such as theft and robbery that can cause loss. In various regions in Indonesia, the rate of theft and robbery is still high, so a good security system is needed so that cases of theft and robbery can be avoided as early as possible. In the era of technology that is developing so rapidly nowadays, there are many breakthroughs in security systems for homes, buildings, and environments that utilize technology, one of which is a security system based on IoT (Internet of Things). In this paper will focus on reviewing the concepts applied by several previous papers relating to security systems for homes, buildings and the environment. Then the results of the review can obtain appropriate and relevant concepts to be applied for home security systems with minimal internet network conditions.